32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-2280
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rotor Models for Wind Turbine Simulations

Abstract: In this paper, air flow around a model wind turbine and the NREL offshore 5-MW baseline wind turbine is simulated using different rotor modeling techniques/methodologies. The actuator line (AL) method of modeling the rotor is compared with the fully resolved rotor simulation. The aerodynamic forces for the AL method are computed using an open source code, FAST, from NREL. An in-house code, Tenasi, is used to carry out the CFD simulations. Validation of the computational methodology is carried out by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The simplest velocity sampling approach might be using the available wind velocity at the nearest fluid point. But as demonstrated in Mittal et al, 3 this approach would result in large oscillations due to the strong blade‐local effects. A more considered approach is to interpolate the velocity to the exact AL point location from nearby fluid points.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The simplest velocity sampling approach might be using the available wind velocity at the nearest fluid point. But as demonstrated in Mittal et al, 3 this approach would result in large oscillations due to the strong blade‐local effects. A more considered approach is to interpolate the velocity to the exact AL point location from nearby fluid points.…”
Section: Introductionmentioning
confidence: 94%
“…The proposed modifications are tested by simulating an NREL‐5MW concept wind turbine 35 . This wind turbine has been extensively studied in many previous works that provide a rich database for comparison 3,21,29 . It is a three‐blade turbine with a diameter of D=126 m. In this work, the rotational speed of 9.155 rpm is considered for a uniform freestream wind speed of 8 m/s, corresponding to a tip‐speed ratio (TSR) of 7.55.…”
Section: Cfd Solver and Case Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALM can exhibit run times similar to a fully resolved rotor simulation due to time-step restrictions required to track the rotation of the actuator lines [40]. Additionally, it shows very similar wake velocity profiles [50] and power predictions [36] to the ADM-R. For these reason, we have chosen to focus on the application of the actuator disk models for this thesis.…”
Section: Actuator Line Modelmentioning
confidence: 99%
“…Mittal et al investigated the effects of including the nacelle in wake model simulations and concluded that there are definite improvements in the wake velocity profiles [40].…”
Section: Computer Implementationmentioning
confidence: 99%